Advanced biophotonics : tissue optical sectioning - Wang, Ruikang K; Tuchin, V. V. (Valeri? Viktorovich) (Boca Raton : CRC Press, 2014)
'This reference provides an overview of optical imaging and manipulation technologies in biophotonics, covering both basic and advanced optical imaging techniques. It reviews the principles and fundamentals of bioimaging and molecular imaging/manipulation techniques. It also presents an overview of instrumentation, basic algorithms, and data processing methods. Accessible to students and researchers, the book discusses a range of application areas, including established and newer methodologies in biotechnology, biomedical engineering, biophysics, medicine, and pharmacology'--
Includes bibliographical references and index.
Keywords: Imaging systems in medicine; Imaging systems in biology; Optical tomography; Photonics